2015
DOI: 10.1155/2015/307424
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Positive Lightning Return Stroke Electric Fields in Different Meteorological Conditions

Abstract: Positive cloud-ground lightning is considerably more complex and less studied compared to the negative lightning. This paper aims to measure and characterize the significant parameters of positive return strokes electric field, namely, the zero-to-peak rise time, 10–90% rise time, slow front duration, fast transition rise time (10–90%), zero-crossing time, and opposite polarity overshoot relative to peak. To the best of the authors’ knowledge, this is the first time such detailed characteristics of positive li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
1
11
2
Order By: Relevance
“…2 and 3 show the samples of waveforms with recorded flash number fitting the BIL and BL models, respectively. This study is similar with that described in [13] where 79% of measurements taken in December 2012 have PBPs, but is different from [14] where 46% of the flashes taken April-June, 2009 have PBPs.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…2 and 3 show the samples of waveforms with recorded flash number fitting the BIL and BL models, respectively. This study is similar with that described in [13] where 79% of measurements taken in December 2012 have PBPs, but is different from [14] where 46% of the flashes taken April-June, 2009 have PBPs.…”
Section: Resultssupporting
confidence: 87%
“…1. The setup is similar to experimental setups used in [4,5,13,14]. The vertical component of electric field was captured using a 1.5m-height parallel plate antenna.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that many counties already reported the PBP preceding positive return stroke [4,6,16,21,22], apart from our own study reported in [23], this is the first time preliminary breakdown preceding positive lightning in Malaysia is reported. The initial polarity of PBP in negative cloud-to-ground (-CG) lightning is always the same as that of the first return stroke.…”
Section: Introductioncontrasting
confidence: 67%
“…As summarized by [20], such percentage apparently varies with latitude. The smallest percentage is 19%, Despite the fact that many counties already reported the PBP preceding positive return stroke [4,6,16,21,22], apart from our own study reported in [23], this is the first time preliminary breakdown preceding positive lightning in Malaysia is reported. The initial polarity of PBP in negative cloud-to-ground (-CG) lightning is always the same as that of the first return stroke.…”
Section: Introductioncontrasting
confidence: 58%